2019
DOI: 10.1016/j.isci.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a Mutant-Induced Receptor Allosteric Mechanism for the Thyroid Hormone Resistance

Abstract: SummaryResistance to thyroid hormone (RTH) is a clinical disorder without specific and effective therapeutic strategy, partly due to the lack of structural mechanisms for the defective ligand binding by mutated thyroid hormone receptors (THRs). We herein uncovered the prescription drug roxadustat as a novel THRβ-selective ligand with therapeutic potentials in treating RTH, thereby providing a small molecule tool enabling the first probe into the structural mechanisms of RTH. Despite a wide distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…A previous report suggested that some drugs, such as the retinoid X receptor-selective ligands, suppress the activity of the TSH gene promoter, thereby causing central hypothyroidism [ 3 ]. Roxadustat has structural similarity with T3 and is a selective activating ligand for thyroid hormone receptor-β, possibly suppressing TSH release [ 4 ]. Moreover, roxadustat can partially cross the blood–brain barrier in mice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report suggested that some drugs, such as the retinoid X receptor-selective ligands, suppress the activity of the TSH gene promoter, thereby causing central hypothyroidism [ 3 ]. Roxadustat has structural similarity with T3 and is a selective activating ligand for thyroid hormone receptor-β, possibly suppressing TSH release [ 4 ]. Moreover, roxadustat can partially cross the blood–brain barrier in mice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…THRβ plays an important role in hypothalamus and pituitary gland. According to Yao et al, roxadustat has a molecular structure similar to T3, and it binds to THRβ at a higher affinity than T3 [ 7 ]. In addition, THRβ has a predominant role in the down-regulation of thyrotropin releasing hormone (TRH) secretion from hypothalamus and TSH secretion from the anterior pituitary gland than THRα[ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Roxadustat has structure similar to triiodothyronine (T3) and also binds to thyroid hormone receptor β (THRβ) at a higher affinity than T3 [ 7 ]. Since THRβ in the pituitary and hypothalamus plays an important role in the feed-back regulation of thyroid hormone [ 8 ], roxadustat may affect the homeostasis of thyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the laboratory of the chemist John Kho synthesized TH analogues able to abrogate the dominant negative effect of the TRb mutants R2320C, R230H and R316H when tested in vitro (49). More recently Yao et al (50) showed that roxadustat, a drug used to treat anemia of renal failure, had 3-to 5-fold higher binding to the TRb mutants V264D, H435L and R438H than T 3 . However, none of these agonists have been tested in vivo.…”
Section: Current and Future Treatment Approachesmentioning
confidence: 99%
“…More recently Yao et al. ( 50 ) showed that roxadustat, a drug used to treat anemia of renal failure, had 3- to 5-fold higher binding to the TRβ mutants V264D, H435L and R438H than T 3 . However, none of these agonists have been tested in vivo .…”
Section: Current and Future Treatment Approachesmentioning
confidence: 99%